SELEÇÃO DIRECIONADA DA Saccharomyces cerevisiae POR ALTA PRESSÃO HIDROSTÁTICA PARA PRODUÇÃO DE ETANOL DE SEGUNDA GERAÇÃO DE CASCA DE COCO VERDE - Vasconcelos, Cárita Turbay (2019)
Coconut palm cultivation covers about 90 countries and Brazil stands out in the production of green coconut, with approximately 50 thousand hectares planted with high productivity and production all year round. This factor, together with the expansion of